2018
DOI: 10.1002/2017tc004633
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Alpine (Variscan) Inheritance: A Key for the Location of the Future Valaisan Basin (Western Alps)

Abstract: The boundary between the Helvetic and the Penninic (=Briançonnais) Zones has long been recognized as a major fault (“Penninic Front”) in the Western Alps. A narrow oceanic domain has been postulated at least along part of this boundary (the Valaisan Basin). However, the information provided by the pre‐Triassic basement has not been fully exploited and will be discussed here in detail. The igneous and metamorphic history of the pre‐Triassic basement shows significant differences between the External Massifs fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 181 publications
(251 reference statements)
4
93
1
Order By: Relevance
“…This dextral shearing can obviously not be related to the Pangea B to A transformation because it predates the Early Permian rocks that yielded the paleomagnetic data on which Pangea B is based (Muttoni et al, ). Whereas dextral shearing during the Carboniferous at ~340–320 Ma is well documented (e.g., Ballèvre et al, ), we found no documentation of fault‐rock kinematics of Permian dextral strike‐slip faults in the Alps. The only exception is the Cossato‐Mergozzo‐Brissago in the westernmost Southern Alps, which is, however, controversial (dextral according to Boriani et al, ; sinistral according to Handy et al, , and Handy & Streit, ).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…This dextral shearing can obviously not be related to the Pangea B to A transformation because it predates the Early Permian rocks that yielded the paleomagnetic data on which Pangea B is based (Muttoni et al, ). Whereas dextral shearing during the Carboniferous at ~340–320 Ma is well documented (e.g., Ballèvre et al, ), we found no documentation of fault‐rock kinematics of Permian dextral strike‐slip faults in the Alps. The only exception is the Cossato‐Mergozzo‐Brissago in the westernmost Southern Alps, which is, however, controversial (dextral according to Boriani et al, ; sinistral according to Handy et al, , and Handy & Streit, ).…”
Section: Discussioncontrasting
confidence: 85%
“…Also shown in Figure is the time span of dextral transcurrent shearing in the External Massives of the Helvetic Zone. In this part of the Alps, dextral shear zones have been dated by Genier et al () at ~320 Ma, by Ballèvre et al () at ~320–310 Ma, and by Simonetti et al () at ~340–320 Ma. Retrodeformation of Alpine deformation results in an original SW‐NE strike for these shear zones.…”
Section: Discussionmentioning
confidence: 93%
“…The Variscan orogeny is widely interpreted as a result of the Carboniferous collision and accretion of Gondwanaderived microcontinents and continental masses with those of Laurussia (Gutiérrez-Alonso et al 2008;Padovano et al 2014). The irregular boundaries of the colliding plates generated coeval transpressional and transtensional tectonics, accompanied by a complex pattern of intracontinental shear zones at the scale of the southern European Variscides (Arthaud and Matte 1977;Neubauer and Handler 2000;Gutiérrez-Alonso et al 2004, 2008Martínez Catalán 2011;Padovano et al 2011Padovano et al , 2014Dias et al 2017;Ballèvre et al 2018; Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…These units are distinct for their Alpine metamorphic evolution and for their internal structure and rock assemblage and they represent the fossil oceanic lithosphere of the Jurassic Tethyan ocean [43,44]. This ocean basin, separating the continental Adriatic/African and European plates, consisted of a main branch known as the Piemonte-Ligurian (or South Penninic) basin, and minor northern branches including the Valaisan (or North Penninic; e.g., see [81][82][83][84]), and the Antrona basins [85][86][87]. These latter two sub-basins were separated by the Briançonnais peninsula preserved in the W Alps [84,88,89] but thinned to the east, so that only one Penninic ocean basin gave rise rise to the ophiolites exposed in the E Alps at/near the Tauern tectonic window [90] (see also the review in [91]).…”
Section: Regional Geological Backgroundmentioning
confidence: 99%
“…This ocean basin, separating the continental Adriatic/African and European plates, consisted of a main branch known as the Piemonte-Ligurian (or South Penninic) basin, and minor northern branches including the Valaisan (or North Penninic; e.g., see [81][82][83][84]), and the Antrona basins [85][86][87]. These latter two sub-basins were separated by the Briançonnais peninsula preserved in the W Alps [84,88,89] but thinned to the east, so that only one Penninic ocean basin gave rise rise to the ophiolites exposed in the E Alps at/near the Tauern tectonic window [90] (see also the review in [91]). This setting is thought to have resulted from an intense fragmentation of the oceanic spreading ridge promoted by regional-scale transform faults, as envisaged in several paleogeographic reconstructions [83,89,92].…”
Section: Regional Geological Backgroundmentioning
confidence: 99%